Adaptation of a β-1,3-Glucanase Assay to Microplate Format - Yuzhi Zheng; Chris A. Wozniak (BioTechniques, 1997)
A method is described for performance of a β-1,3-glucanase assay in microplates. The adaptation to microassay format has been made possible through the availability of heat-stable microplates. Assay samples containing β-1,3-glucanase (cell extracts) and the substrate are mixed in 96-well, autoclavable microplates. Incubation of the enzyme-substrate mixture results in the release of reducing sugars by the action of β-1,3-glucanase. The levels of these sugars are colorimetrically quantified through the addition of “copper reagent” and neocuproine, incubation at 100°C for 10 min and the resulting reduction of Cu++ to Cu+. A standard curve of glucose concentrations within the same plate allows for assessment of internal variance. Twenty samples can be assayed in one microplate in 1 h, compared to the 96 test tubes and 4 h needed for traditional assay methods. The net savings in reagents used with the microplate format is substantial. The measurement of optical density is performed rapidly for all of the samples, eliminating the problem of oxidization of Cu+ to Cu++ during quantification. This method represents a significant savings in time, chemicals and cost.